Effect of phosphate-buffered saline on push-out bond strength of a new bioceramic sealer to root canal dentin - Noushin Shokouhinejad; Atefeh Hoseini; Hedayat Gorjestani; Maryam Raoof; Hadi Assadian; Ahmad Reza Shamshiri (Wolters Kluwer Medknow Publications, 2012)
Background: The aim of this study was to compare push-out bond strength of a new bioceramic endodontic sealer, EndoSequence BC sealer (Brasseler USA, Savannah, GA), used with gutta-percha in the presence or absence of phosphate-buffered saline solution (PBS) within the root canals. Materials and Methods: Forty single-rooted human teeth were prepared and randomly divided into four groups. Samples in groups 1 and 2 were dried, but those in groups 3 and 4 were moistened with PBS before obturation. All root canals were obturated with gutta-percha/EndoSequence BC sealer. The specimens were stored in PBS for 7 days in groups 1 and 3 and for 2 months in groups 2 and 4. Push-out bond strength values and failure modes were evaluated. The data on push-out bond strength were analyzed using two-way ANOVA. Results: The mean value for the bond strength of the obturation material in moistened canals was significantly higher than that in dried ones at 1 week (P = 0.00). Contrarily, there was no significant difference between dried and moistened root canals at 2 months (P = 0.61). In dried canals, bond strength increased significantly with time but in moistened ones, the difference was not significant. Inspection of the specimens revealed the bond failure to be mainly cohesive for all groups. Conclusion: The presence of PBS within the root canals increased the bond strength of EndoSequence BC sealer/gutta-percha at 1 week. However, no difference was found between the bond strength of EndoSequence BC sealer/gutta-percha in the presence or absence of PBS in the root canals at 2 months.